Is Alexithymic Individual Truly That Numb? Relationship Between Alexithymia and Loss Aversion Among Early Adulthood - Hanifah, Baya Qalbu; Afiati, Nikmah Sofia (Jurnal Psikologi Karakter, 2024)
Departing from Previous research, it was hypothesized that alexithymia is associated with higher loss tolerance. This hypothesis was then extended by linking it to other personality traits related to risk taking which resulted in similar results. In this current study, this assumption is evaluated using a different approach to loss aversion where loss aversion in this research is seen as a trait rather than a state. it was then discovered that alexithymia and loss aversion had a positive directional relationship along with the Pearson correlation coefficient (r) of 0.302 and p value <0.001 obtained. The finding on a coefficient of determination (R²) of 0.0927 also strengthens the influence of alexithymia on loss aversion by a bit. Explanations for results that are contrary to the previous hypothesis as well as various possible causes are also discussed in this research.